Digital Autism in the Age of Smartphones: A Review of Neurological, Behavioural, and Cognitive Effects (Journal of Cortexplore, 2026)
The ubiquity of smartphones in contemporary life is reshaping how people think, feel, and interact, with growing evidence suggesting that excessive screen exposure can disrupt cognitive and emotional development—particularly in children and adolescents. Emerging research frames "Digital Autism" as a metaphor for autism-like behaviors resulting from prolonged device use, including diminished social reciprocity, deficits in empathy, and fragmented attention, though it is not a formal diagnosis. This review synthesizes interdisciplinary findings from 2015 to 2025, aggregating studies sourced from major scholarly databases to investigate the neurological, behavioral, and cognitive consequences of heavy smartphone use. Using a hybrid systematic-narrative approach under PRISMA 2020 guidelines, seventy empirical and meta-analytic studies were analyzed according to domains of neurological function, behavior, and cognition, with attention to age, exposure duration, parental mediation, and socio-cultural context. The results indicate that chronic smartphone exposure alters neural regions governing executive control, attention, and social cognition, while also promoting emotional dysregulation, social withdrawal, communication delays, and impairments in working memory and attentional focus. "Digital Autism" thus offers a heuristic framework for understanding environmental neuroplasticity in response to digital overstimulation, underscoring the urgent need for coordinated action by educators, clinicians, and policymakers to advance digital well-being in children and adolescents facing cognitive saturation.DOI: doi.org/10.65320/jce.vol.1.issue1.5
Keywords: Digital Autism; Smartphone Overuse; Cognitive Development; Neuroplasticity; Behavioral Effects; Child Development